ADAPTASI DAN EFEK STRES PADA FAMILY CAREGIVER SKIZOFRENIA - Anindya Arum Cempaka; Maria Theresia Arie Lilyana; Agustina Chriswinda Bura Mare; Ira Maryuti (JPK : Jurnal Penelitian Kesehatan, 2026)
Introduction: Schizophrenia is a mental disorder characterized by changes in mental function that disrupt life functions, thus decreasing quality of life. Schizophrenia not only affects the individual suffering from the disease but also family caregivers. Caring for a schizophrenic patient at home can lead to the burden of care and emotional disturbances such as shame, guilt, and even depression. Therefore, the ability to care for a sick family member until complete recovery is essential. Objective: This study aims to explore the forms of adaptation and the effects of stress experienced by family caregivers when caring for a family member with schizophrenia. Method: A qualitative phenomenological study was chosen to explore the experiences of caregivers, including the forms of adaptation and the effects of stress experienced by family caregivers when caring for their relatives with schizophrenia. Five respondents who cared for schizophrenia patients and met the criteria participated in this study. Data collection was recorded with a voice recorder and transcribed verbatim. Colaizzi analysis was conducted to identify themes in the research results and narrated them for understanding. Results: The themes of the research results are: 1) Forms of adaptation carried out by family caregivers when facing stress; 2) The impact of stress on family caregivers with schizophrenia. Conclusion: Family caregivers use emotion-focused coping strategies to reduce stress, including watching television and praying. Caring for family members has psychological consequences, requiring medical intervention from a psychiatrist, and physical consequences, including digestive problems in family caregivers. Therefore, psychoeducational programs, peer support groups, and family counseling are needed to improve caregiver adaptation. Further research should explore culturally and spiritually based interventions relevant to the Indonesian family context to reduce stress levels in family caregivers with schizophrenia.